Pengembangan Media Pembelajaran Interaktif Mata Pelajaran PAI Berbasis Android - Arifin, Zaenal (Education Mind Based Development Association, 2025)
This study aims to develop an interactive learning media based on Android for Islamic Religious Education (PAI) subjects and analyze its implications in enhancing learning effectiveness. The research method used is research and development (R&D) with the Borg & Gall model, which includes stages of research and data collection, planning, initial product development, product validation, revision, trials, further revision, and dissemination. The results show that the development of Android-based learning media through needs analysis, product design, expert validation, student trials, as well as product revision and refinement produces an effective media. Student responses to this learning media indicate a feasibility level of 97%, meaning that the application is highly suitable for use in learning. Interactive Android-based learning media has been proven to increase student engagement and understanding in PAI learning, particularly in Qur’an Hadith material.